Thermally Resistive Electrospun Composite Membranes for Low-Grade Thermal Energy Harvesting - Hasan, Syed Waqar; Said, Suhana Mohd; Sabri, Mohd Faizul Mohd; Jaffery, Hasan Abbas; Shuhaimi, Ahmad (John Wiley & Sons, 2018)
In this work, thermally insulating composite mats of poly(vinylidene fluoride) (PVDF) and polyacrylonitrile (PAN) blends are used as the separator membranes. The membranes improve the thermal-to-electrical energy conversion efficiency of a thermally driven electrochemical cell (i.e., thermocell) up to 95%. The justification of the improved performance is an intricate relationship between the porosity, electrolyte uptake, electrolyte uptake rate of the electrospun fibrous mat, and the actual temperature gradient at the electrode surface. When the porosity is too high (87%) in PAN membranes, the electrolyte uptake and electrolyte uptake rate are significantly high as 950% and 0.53 µL s−1, respectively. In such a case, the convective heat flow within the cell is high and the power density is limited to 32.7 mW m−2. When the porosity is lesser (up to 81%) in PVDF membranes, the electrolyte uptake and uptake rate are relatively low as 434% and 0.13 µL s−1, respectively. In this case, the convective flow shall be low, however, the maximum power density of 63.5 mW m−2 is obtained with PVDF/PAN composites as the aforementioned parameters are optimized. Furthermore, multilayered membrane structures are also investigated for which a bilayered architecture produces highest power density of 102.7 mW m−2.